Problems and Solutions in Combustion Performance Test of Building External Thermal Insulation Materials - Chunshan Peng, Jingjing Li, Junwei Li (Forest Chemicals Review, 2022)
The quality of building external thermal insulation materials is related to the safety of buildings. With the development of high-rise building thermal insulation materials, people pay more and more attention to the combustion performance. The test results also play a guiding role in whether this type of material can be used in practical engineering. Therefore, it is very important to test its combustion performance. From the current situation of combustion performance testing of external thermal insulation materials, there are still some problems. This requires effective countermeasures. This paper focuses on the problems and Countermeasures of combustion performance detection of building external thermal insulation materials This paper expounds the classification of combustion performance of building materials and their products and the main parameters of material combustion performance affecting fire, and briefly analyzes the main problems and Measures Existing in the detection of combustion performance of building external thermal insulation materials. The application of organic materials in building exterior wall insulation system has obtained very good combustion performance, and this material accelerates the spread of fire on the premise of fire. Therefore, strengthening the combustion performance of organic thermal insulation materials is one of the concerns.